Catch Efficiency of Cast Nets for Snow Trout Fishing in Dal Lake, Kashmir - Azhar, Mudassir; Edwin, Leela; Manoj Kumar, B.; Thomas, Saly N.; Remesan, M. P. (Fishery Technology, 2020)
Experimental cast net fishing was carried out in theDal Lake of Kashmir to study the catching efficiency,species wise catch composition and size frequency.In terms of fish caught by numbers, cast net TypeII monofilament stringed landed 107 fishes and TypeI monofilament stringless landed 104 fishes. Multifilamentstringed net caught 65 fishes and multifilamentstringless net caught only 64 fishes out of50 operations of each cast net. Four species of snowtrout were caught in experimental operations.During the study the monofilament cast nets werefound to have better catching efficiency than themultifilament cast nets.